Molecular typing of canine parvovirus with PCR assay based on genetic markers of the antigenic variants - SINGH, DEEPTI; VERMA, AMIT KUMAR; KUMAR, AMIT; SRIVASTAVA, MUKESH KUMAR (The Indian Journal of Animal Sciences, 2015)
The canine parvovirus (CPV) is prevalent in India but only scanty literature is available on molecular differentiation of its strain using polymerase chain reaction. In the present study, 100 faecal samples from dogs suspected for canine parvo virus infection (gastroenteritis) were collected and processed for isolation of viral genomic DNA. Molecular test like PCR assay using 3 specific pairs of primers (pCPV-RT, pCPV-2ab and pCPV- 2b) was conducted for differential diagnosis of the virus type. Out of 100 faecal samples, 63 were positive for presence of CPV, of which 54 were CPV-2b and 9 were CPV-2a, indicating the predominance of CPV-2b virus type.